Experimental study on strength of spot welded - Hasbullah, Ishak (2009)
In this paper, the objective is to investigate the strength of spot welding using variable thickness of sheet metal, weld time and weld current. Spot welded of the same material and different thickness combinations by overlapping joint were welded together to form a single spot. Thus, mild steel sheet of thickness 1.2mm and 1.5mm were studied and combined to form spot welded. Different parameters of welding such as welding current and welding time were used to weld the sheet metal for each thickness. Then tensile test machine was used to test the formability of spot welded and follow up by image analyzer testing to capture the image of spot welded nugget. The tensile test show that, the optimum parameter are at condition (T = 1.2mm, t = 3sec & I =5A) which produced 5.958kN of loading. The experimental findings show that resistance spot welding of different types of parameters and also different thickness of sheet metal shows different strength.